2016
DOI: 10.1007/s00266-016-0652-7
|View full text |Cite
|
Sign up to set email alerts
|

Autoaugmentation Mastopexy Modification Prevents Bottoming-Out Deformity and Areola Distortion: A Preliminary Report

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“… 16 All other studies incorporating the vertical reduction pattern reported the elongation of the lower inframammary pole length, bottoming out, or increase in pseudoptosis over the study period. 2 , 6 , 9 , 17 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 All other studies incorporating the vertical reduction pattern reported the elongation of the lower inframammary pole length, bottoming out, or increase in pseudoptosis over the study period. 2 , 6 , 9 , 17 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…These include pillar sutures, permanent and absorbable meshes, lipofilling, dermal or dermoglandular slings, autoaugmentation flaps, and muscular slings. 2 , 3 , 4 , 6 , 9 , 11 , 15 , 16 , 17 , 18 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 The meshes used were variable and permanent or partially absorbable meshes generally had better outcomes compared to fully absorbable meshes. Hamdi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first reports of autologous parenchymal flaps in the 1970s (14,15), numerous techniques with only subtle variations were published. These include variations regarding incision patterns, orientation of the pedicle and fixation maneuver (2)(3)(4)(15)(16)(17). Further techniques propose the additional use of tissue from the back, referred to as thoracic wall flaps, that are especially popular in massive weight loss patients (5,18).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, various techniques that differ in the incision pattern and dermoglandular pedicle have been proposed under the term "Autoaugmentation" mastopexy (3,4,8,9). In our department, an inferior based dermoglandular flap proposed by Graf and Biggs was used (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation